Higher Serum Asprosin Level is Associated with Urinary Albumin Excretion and Renal Function in Type 2 Diabetes - Deng X (Dove Medical Press, 2020)
Xia Deng, Li Zhao, Chang Guo, Ling Yang, Dong Wang, Yanyan Li, Hong Xia, Chenxi Wang, Zhensheng Cai, Lian Li, Zhicong Zhao, Guoyue Yuan Department of Endocrinology, Affiliated Hospital of Jiangsu University, Zhenjiang, Jiangsu 212001, People’s Republic of ChinaCorrespondence: Guoyue Yuan; Zhicong ZhaoDepartment of Endocrinology, Affiliated Hospital of Jiangsu University, 438 Jiefang Road, Zhenjiang, Jiangsu 212001, People’s Republic of ChinaTel +86-13505289352; +86-18752965615Email yuanguoyue@ujs.edu.cn; 2211517025@stmail.ujs.edu.cnAim: We detected whether serum asprosin levels play a role in the occurrence and development of albuminuria in patients with type 2 diabetes mellitus (T2DM), which has not been previously discussed.Methods: Based on urinary albumin/creatinine ratio (UACR), 207 T2DM patients were divided into T2DM patients with normoalbuminuria (UACR< 30 mg/g), microalbuminuria (30≤UACR< 300 mg/g), and macroalbuminuria (UACR≥ 300 mg/g). Serum asprosin levels were determined by enzyme-linked immunosorbent assay.Results: Comparatively, the serum asprosin levels in T2DM patient groups with macroalbuminuria [2.37 (1.63– 3.57)] and microalbuminuria [2.10 (1.60– 2.90)] were significantly increased than the normoalbuminuria group [1.59 (1.18– 2.09)] (P< 0.001). Importantly, the serum level of asprosin was positively correlated with UACR (r=0.304, P< 0.001), creatinine (r=0.157, P=0.024), blood urea nitrogen (BUN) (r=0.244, P< 0.001), and negatively with glomerular filtration rate (eGFR) (r=− 0.159, P=0.022). Furthermore, multiple stepwise regression analyses showed that asprosin was significantly and independently related to UACR, BUN, DBP, and LDL-C (P< 0.05). Besides, after adjustment for the confounders, the serum asprosin level was constantly and independently associated with the development of albuminuria in T2DM patients [OR (95% CI): 2.003 (1.37∼ 2.928), P < 0.001].Conclusion: Obviously, the serum asprosin level was independently correlated with UACR in T2DM patients, which implies circulating asprosin may play an essential role in the pathogenesis of diabetic nephropathy.Keywords: asprosin, type 2 diabetes mellitus, diabetic nephropathy